A review on perovskite materials for photovoltaic applications - Lalruat Sanga; Celestine Lalengmawia; Zosiamliana Renthlei; Sougaijam Thasana Chanu; Lalhum Hima; Ningthoujam Surajkumar Singh; Andre Yvaz; Sagar Bhattarai; D.P. Rai (Next Materials)
Perovskite materials have been intensively studied and successfully employed in solar application fields. However, as the reason of their instability in its structure and the presence of toxic elements like lead element (Pb), the performance of these materials has been hindering the production and successful manufacturing of perovskite solar cells (PSCs) at the commercial level. Researchers have been exploring numerous types of materials which seek the results of augmenting the optical properties and performances of the perovskite materials to pave the way to obtain and successfully fabricate and manufacture cost-effective and environmentally friendly perovskite photovoltaic cells. To successfully develop and engineer PSCs for commercialization, it is imperative to have a clear insight into the performance of the material, the features and weaknesses to be addressed for specific types in the field with which necessary improvements could be made. Herein, we report a brief review among the various emerging perovskite materials for photovoltaic applications to gain knowledge of the properties and characteristics of perovskites for utilization in solar cells and its future scope by which we could ultimately decide what measures and changes need to be done in the PV world.